Deletions of ttrA and pduA genes in Salmonella enterica affect survival within chicken-derived HD-11 macrophages - Saraiva, Mauro M. S. [UNESP] (2024)
In mammals, enteric salmonellas can use tetrathionate (ttr), formed as a by-product from the inflammatory process in the intestine, as electron acceptor in anaerobic respiration, and it can fuel its energy metabolism by degrading the microbial fermentation product 1,2-propanediol. However, recent studies have shown that this mechanism is not important for Salmonella infection in the intestine of poultry, while it prolongs the persistence of Salmonella at systemic sites in this species. In the current study, we show that ΔttrApduA strains of Salmonella enterica have lower net survival within chicken-derived HD-11 macrophages, as CFU was only 2.3% (S. Enteritidis ΔttrApduA), 2.3% (S. Heidelberg ΔttrApduA), and 3.0% (S. Typhimurium ΔttrApduA) compared to wild-type strains after 24 h inside HD-11 macrophage cells. The difference was not related to increased lysis of macrophages, and deletion of ttrA and pduA did not impair the ability of the strains to grow anaerobically. Further studies are indicated to determine the reason why Salmonella ΔttrApduA strains survive less well inside macrophage cell lines. Graphical abstract: (Figure presented.)